PC (polycarbonate) composition as well as preparation method and application thereof

By introducing cellulose nanocrystals and sulfone polymers into PC resin to form a heterogeneous organic structure, the problems of insufficient chemical resistance and poor temperature resistance of PC materials in contact with polar solvents and organic components are solved, and the high toughness and high heat resistance of the material are achieved.

CN120888173APending Publication Date: 2025-11-04KINGFA SCI & TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202511215299.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-28
Publication Date
2025-11-04

AI Technical Summary

Technical Problem

Existing PC materials have insufficient chemical resistance when in contact with polar solvents or mixed organic components, and poor temperature resistance, making them prone to cracking or degradation of mechanical properties.

Method used

By introducing cellulose nanocrystals and sulfone polymers into PC resin and controlling the aspect ratio of the retained cellulose nanocrystals to be 20-30, a heterogeneous organic structure is formed, which enhances the chemical resistance and high and low temperature resistance of the material.

Benefits of technology

It significantly improves the chemical resistance and high and low temperature resistance of PC materials, ensuring high toughness retention at low temperatures, high heat distortion temperature, and excellent overall performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005570079750000091
    Figure BDA0005570079750000091
  • Figure BDA0005570079750000101
    Figure BDA0005570079750000101
Patent Text Reader

Abstract

The invention discloses a PC (polycarbonate) composition and a preparation method and application thereof, and belongs to the technical field of high polymer materials, the composition is compounded by introducing cellulose nanocrystals and sulfone polymers into PC resin, so that the chemical resistance of a product can be effectively improved, the product can still maintain stability after being in contact with various organic components, and the stability of the product is improved. Meanwhile, the high and low temperature resistance is remarkably improved, the toughness retention rate of the product at low temperature is high, the thermal deformation temperature is high, and the comprehensive performance is excellent.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of high polymer materials, in particular to a PC composition, a preparation method and application thereof. BACKGROUND

[0002] PC (polycarbonate) has good processing performance and mechanical strength, and is widely used in various application scenarios. However, the current PC material still has some defects in some application scenarios. For example, in some scenarios that need to contact polar solvents or mixed organic components (such as food, cosmetics, chemical solvent storage devices), due to the poor chemical resistance of the PC material, the product may be corroded by the organic components, and in severe cases, even cracking phenomenon may occur. On the other hand, the current PC material has poor temperature resistance, and the usable temperature range is narrow. In some low or high temperature working environments, the mechanical properties may decrease (such as low temperature toughness failure) or deformation (high temperature deformation) defects may occur. SUMMARY

[0003] Based on the defects of the prior art, the purpose of the present application is to provide a PC composition. The composition is compounded by introducing cellulose nanocrystals and sulfone polymers into the PC resin, which can effectively improve the chemical resistance of the product, so that it can remain stable after contacting various organic components. At the same time, the high and low temperature resistance is significantly improved, the toughness retention rate of the product at low temperature is high, the heat distortion temperature is high, and the comprehensive performance is excellent.

[0004] In order to achieve the above purpose, the technical scheme adopted by the present application is as follows:

[0005] A PC composition, comprising the following components by weight:

[0006] PC resin 60-70 parts, cellulose nanocrystals 1-20 parts, sulfone polymer 30-50 parts;

[0007] The retention aspect ratio of the cellulose nanocrystals is 20-30.

[0008] Cellulose nanocrystals (CNC) is a special material that can gradually self-assemble into a cholesteric phase liquid crystal state with left-handed helical nanostructure. The inventors have found that, compared with microcrystalline cellulose or other types of compounded filler ingredients, CNC has greater chemical inertness and more excellent chemical solvent resistance, especially when it is introduced into a PC resin and a sulfone polymer blended organic system, and the final retention aspect ratio of the ingredient is optimized to the above defined range, CNC can achieve high dispersibility, and due to the good chemical corrosion resistance of the sulfone polymer itself, CNC and the sulfone polymer synergistically improve the chemical resistance of the PC resin. On the other hand, after the sulfone polymer is compounded with the PC resin, a heterogeneous organic structure is formed, and at this time, CNC with the retention aspect ratio can be stacked into a highly dispersed three-dimensional configuration with the organic phase structure, fully playing the role of a "reinforcing bar" in support and enhancement. When the product is at a lower temperature, it can inhibit the shrinkage of the organic phase to some extent, and fully transfer and disperse when the product is subjected to external stress, thereby enhancing the external force bearing degree of the product, so that the toughness of the product at a lower temperature can still be maintained at a considerable degree. At high temperature, the ingredient still has good dimensional stability, so it can maintain the mechanical support strength of the product, and the high temperature resistance of the sulfone polymer, which synergistically improves the heat resistance of the product, so that the pressure thermal deformation temperature of the product is higher.

[0009] If the retention aspect ratio of CNC in the product is too large or too small, not only will the dispersibility of the ingredient in the product be low, but also the excellent three-dimensional skeleton support characteristics cannot be achieved, which will affect the low and high temperature resistance of the product, and the chemical resistance will also be affected, so it needs to be strictly controlled within the range of 20-30.

[0010] Preferably, the melt flow rate of the PC resin at 300℃ under a load of 1.2kg is 6-18g / 10min.

[0011] Further preferably, the melt flow rate of the PC resin at 300℃ under a load of 1.2kg is one of 6g / 10min, 7g / 10min, 10g / 10min, 12g / 10min, 16g / 10min, 18g / 10min or a range value of any two thereof.

[0012] The melt flow rate of the PC resin in the technical solution of the present application is not particularly limited, and those skilled in the art can select different PC resins according to the use requirements of the product, as long as it does not affect the chemical solvent resistance and high and low temperature resistance of the product.

[0013] Preferably, in the PC composition, the weight fraction of the PC resin is one or a range value of any two of 60 parts, 62 parts, 64 parts, 66 parts, 68 parts, 70 parts, the weight fraction of the cellulose nanocrystal is one or a range value of any two of 1 part, 2 parts, 3 parts, 5 parts, 8 parts, 10 parts, 12 parts, 14 parts, 16 parts, 18 parts, 20 parts, and the weight fraction of the sulfone polymer is one or a range value of any two of 30 parts, 32 parts, 35 parts, 38 parts, 40 parts, 42 parts, 45 parts, 48 parts, 50 parts.

[0014] Further preferably, the PC composition comprises the following components by weight:

[0015] PC resin 62-68 parts, cellulose nanocrystal 8-12 parts, sulfone polymer 35-45 parts.

[0016] Preferably, in the PC composition, the mass percentage of the PC resin is ≥40wt%.

[0017] Preferably, the PC resin comprises at least one of a silicon copolymer PC resin and a bisphenol A copolymer PC resin.

[0018] The PC composition of the present application is not particularly limited in the type of PC resin in its components. In the preparation of the product, a conventional bisphenol A copolymer PC resin can be selected, and a copolymer PC resin prepared by a phosgene method or a copolymerization method can also be selected. A silicon copolymer PC resin with better corrosion resistance known to those skilled in the art can also be used, and various different PC resins can also be used in blending. As long as the use of the PC resin does not affect the chemical solvent resistance and high and low temperature resistance of the final product, it is not limited.

[0019] More preferably, the mass content of siloxane in the silicon copolymer PC resin is 2-20wt%.

[0020] Specifically, the mass content of siloxane in the silicon copolymer PC resin can be tested by inductively coupled plasma emission spectrometry combined with nuclear magnetic resonance method. Specifically, the mass content of silicon element in the sample is first confirmed by inductively coupled plasma emission spectrometry, and then the type and molecular weight of siloxane in the sample are determined by nuclear magnetic resonance wave. Finally, the mass content of siloxane in the sample is calculated by the mass content of silicon element.

[0021] Preferably, the cellulose nanocrystal is a chiral cellulose nanocrystal.

[0022] The cellulose material is abundant in nature, and the cost of exploitation and processing is low, and the operation is simple. The cellulose nanocrystal is one of the products, which can be prepared by various simple and easy-to-operate methods including enzyme hydrolysis method, acid hydrolysis method, ultrasonic method, and has basically been industrialized. The person skilled in the art can purchase according to the actual situation, or can be prepared by a conventional method.

[0023] The technical scheme of the present application does not limit the source of the cellulose nanocrystal of the PC composition. Specifically, the cellulose nanocrystal can be prepared by acid hydrolysis method, and the preparation method comprises the following steps:

[0024] The precursor material is soaked in a dilute sulfuric acid solution. After dilution, standing, removing the supernatant, centrifugation, interception, purification, concentration and drying culture, the cellulose nanocrystal is obtained.

[0025] More preferably, the precursor material comprises at least one of defatted cotton, pine, bamboo, and flax.

[0026] More preferably, the average polymerization degree of the precursor material is 50-200.

[0027] More preferably, the concentration of the dilute sulfuric acid solution is 60-70wt%.

[0028] More preferably, the temperature of the soaking is 40-50℃, and the soaking time is 60-120min.

[0029] More preferably, the ratio of the mass of the precursor material to the volume of the sulfuric acid solution is 1g:(5-15)mL.

[0030] Further, the average molecular weight of the cellulose nanocrystal is 15500-17000g / mol.

[0031] The average molecular weight of the cellulose nanocrystal can be confirmed as follows: since the basic repeating unit of the nanocrystalline cellulose is glucose, the molecular weight of the repeating unit is 162g / mol. According to the average polymerization degree D of the precursor material, the average molecular weight of the cellulose nanocrystal is calculated as 162g / mol x D.

[0032] It is known to those skilled in the art that the concentration of acid solution, reaction temperature, reaction time and liquid-solid ratio and other parameters will affect the degree of hydrolysis of the amorphous region during the separation and hydrolysis process of the cellulose in the precursor material by using the strong acid hydrolysis method, thereby resulting in the length and diameter of the cellulose nanocrystals obtained, specifically, as the concentration of the strong acid solution increases, the hydrolysis reaction rate increases, the acid solution can more effectively remove the amorphous region of the cellulose, thereby resulting in the length and diameter of the cellulose nanocrystals obtained being reduced, and an increase in temperature also has a similar effect, and appropriately increasing the temperature is beneficial to the hydrolysis of the amorphous region, based on the difference in the degree of transverse and longitudinal hydrolysis, the length of the cellulose nanocrystals is increased compared to that at low temperature, thereby increasing the aspect ratio, but if the temperature continues to rise, the reaction activity is further increased, the transverse and longitudinal hydrolysis rates are both increased, and the aspect ratio of the cellulose nanocrystals is reduced due to the change in structure. Those skilled in the art can select and control the parameters of the preparation process based on the actual situation when obtaining cellulose nanocrystals in a self-made manner, and no special limitation is made thereto.

[0033] Preferably, the rotation speed during centrifugation is 4000-6000 rpm, and the time for single centrifugation is 4-6 min.

[0034] Preferably, the molecular weight cut-off of the dialysis device used during dialysis is 8000-14000.

[0035] Preferably, the temperature during drying culture is 20-30℃, and the time is 40-60 h.

[0036] It should be noted that the retention aspect ratio of the cellulose nanocrystals of the present application is not the same as the original aspect ratio of the cellulose nanocrystals, and during the processing of the PC composition, based on the procedures such as material stirring or mixing processing, the retention aspect ratio of the cellulose nanocrystals in the product is different from the original aspect ratio thereof, in order to ensure the performance of the product during use, the retention aspect ratio thereof is used as the criterion in the present application.

[0037] Preferably, the retention aspect ratio of the cellulose nanocrystals is one of 20, 22, 24, 25, 26, 27, 28, 30 or a range value of any two thereof.

[0038] More preferably, the retention aspect ratio of the cellulose nanocrystals is 20.1-29.3.

[0039] More preferably, the retention aspect ratio of the cellulose nanocrystals is 24-28.

[0040] When the cellulose nanocrystals play the role of reinforcing framework in the PC composition of the present application, if the aspect ratio of the retained length and diameter is further preferably within the above range, the internal organic molecules will have higher regularity and uniformity in the process of thermal expansion and contraction when the product is cooled or heated, and the local softening or local polycondensation will not occur, and the stress effect is better, thus the product can exhibit better high and low temperature resistance.

[0041] More preferably, in the PC composition, the retained average length of the cellulose nanocrystals is about 200-400 nm, and the retained average diameter is about 10-15 nm.

[0042] Specifically, in the PC composition, the retained average length of the cellulose nanocrystals is about 205-370 nm, and the retained average diameter is about 10-12.5 nm.

[0043] More preferably, in the PC composition, the test method of the retained average length, the retained average diameter and the aspect ratio of the cellulose nanocrystals is as follows:

[0044] The PC composition is immersed in dimethyl sulfoxide and ultrasonically treated for 60 min, filtered, and the obtained solid is immersed in chloroform solution and ultrasonically treated for 60 min to remove the sulfone polymer and the PC resin in turn, and then filtered. The remaining material is dispersed in ethanol solution (v50:50), centrifuged, dried, and the obtained powder is dispersed in ethanol, and then a transmission electron microscope observation sample is prepared. The cellulose nanocrystals are observed under a transmission electron microscope at a magnification of 20k, and 200 cellulose nanocrystals are randomly selected and their length and diameter are tested using a measurement software (when testing the diameter, the diameters of the head, tail and middle of the cellulose nanocrystals are tested and the average value is taken as the diameter result of a single cellulose nanocrystal), and the retained length and diameter of the cellulose nanocrystals in the product are obtained. Then the aspect ratio is calculated, and the average value of the aspect ratio of 200 samples is the retained aspect ratio of the cellulose nanocrystals.

[0045] It should be noted that the components of the product of the present application further include 0.01-10 parts of a functional additive, more preferably, the functional additive includes a lubricant, an antioxidant, a flame retardant, an antistatic agent, etc., and a person skilled in the art can add according to actual needs as long as it does not affect the expected technical effect of the product of the present application.

[0046] Preferably, the sulfone polymer includes at least one of polysulfone (PSU), polyphenylsulfone (PPSU) and polyether sulfone (PES).

[0047] More preferably, the sulfone polymer includes polyphenylsulfone.

[0048] Preferably, the sulfonyl polymer has a melt index of 15-50 g / 10 min at 365 DEG C under a load of 5 kg according to the ISO 1133-2011 standard.

[0049] More preferably, the sulfonyl polymer has a melt index of 17-45 g / 10 min at 365 DEG C under a load of 5 kg.

[0050] More preferably, the sulfonyl polymer has a melt index of 25-30 g / 10 min at 365 DEG C under a load of 5 kg.

[0051] As described above, the sulfonyl polymer is compatible with the PC resin itself, and can effectively provide a good organic phase structure for the construction of a three-dimensional skeleton structure of cellulose nanocrystals, and when the sulfonyl polymer is mainly composed of polyphenylene sulfone, the organic phase compounding effect of the product is better, and the chemical solvent resistance and high and low temperature resistance of the product can be further improved.

[0052] On the other hand, the organic phase structure of the product is different with the flowability of the sulfonyl polymer, and when the melt index is preferably in the range of 20-30 g / 10 min, the organic phase structure constructed by the sulfonyl polymer is more suitable for the cellulose nanocrystals in the aspect of the aspect ratio range, and the high and low temperature resistance of the product will be further improved.

[0053] Another object of the present application is to provide a preparation method of the PC composition, comprising the following steps:

[0054] After the components are uniformly mixed, melt extrusion granulation is carried out in a screw extruder, and the PC composition is obtained.

[0055] The preparation method of the conductive PC alloy has simple operation steps and can realize industrialized scale production.

[0056] Preferably, the temperature range of the screw extruder is 250-280 DEG C, the screw rotation speed is 400-600 r / min, and the screw length-diameter ratio is (45-50):1.

[0057] Another object of the present application is to provide the application of the PC composition in the preparation of shell packaging materials.

[0058] Preferably, the shell packaging material comprises any one of automobile shell parts, electronic and electrical shell parts, food packaging shells, and daily chemical product packaging shells.

[0059] More preferably, the automobile shell parts include instrument panels, automobile lamp shells, and the electronic and electrical shell parts include power supply shells, junction boxes, and socket shells.

[0060] A further object of the present application is to provide a shell packaging material comprising the PC composition of the present application.

[0061] The PC composition of the present application has ideal comprehensive performance, not only has ideal chemical solvent resistance, but also has good high and low temperature resistance, can effectively avoid corrosion and pollution of materials such as hand cream and peanut oil when used for packaging food or daily chemical products, can prevent the erosion of chemicals such as rust-proof oil and lubricating oil when used as a shell part of an automobile or an electrical appliance, and can realize a small change range of toughness at a low temperature compared with at room temperature, without low-temperature toughness failure, and has a high heat distortion temperature and good heat resistance.

[0062] The PC composition of the present application has the beneficial effects that the PC composition of the present application is compounded by introducing cellulose nanocrystals and a sulfone polymer into a PC resin, can effectively improve the chemical resistance of the product, can remain stable after contacting with various organic components, has significantly improved high and low temperature resistance, has a high toughness retention rate at a low temperature and a high heat distortion temperature, and has excellent comprehensive performance. DETAILED DESCRIPTION

[0063] In order to better illustrate the purposes, technical solutions and advantages of the present application, the present application will be further described below in combination with specific examples and comparative examples, and the purpose is to understand the content of the present application in detail, rather than to limit the present application. All other examples obtained by those of ordinary skill in the art without creative labor fall within the protection scope of the present application. The experimental reagents and instruments involved in the implementation of the present application are common ordinary reagents and instruments unless otherwise specified.

[0064] Examples 1-12

[0065] The PC composition of the present application and the preparation method and application examples thereof, and the component ingredients of the PC composition are shown in Table 1.

[0066] The preparation method of the product comprises the following steps:

[0067] The components are uniformly mixed, and then placed in a screw extruder for melt extrusion and granulation to obtain the conductive PC alloy.

[0068] The temperature zones of the screw extruder are set as follows: 1 zone: 250℃, 2 zone: 250℃, 3 zone: 255℃, 4 zone: 260℃, 5 zone: 265℃, 6 zone: 265℃, 7 zone: 270℃, 8 zone: 275℃, 9 zone: 280℃, 10 zone: 270℃, the screw rotation speed is 500r / min, and the length-diameter ratio is 48:1; the double vacuum mode is set during the processing, and the vacuum degree is -0.07 to -0.08MPa.

[0069] Comparative Examples 1-7

[0070] The difference between each comparative example and each example is only in the component type and the ratio, as shown in Table 2.

[0071] In the components of each example and comparative example,

[0072] PC resin 1 is PC 2070 produced by Wanhua Chemical, and the melt flow rate under 300℃, 1.2kg is 7g / 10min;

[0073] PC resin 2 is PC S-2000VR produced by Mitsubishi Engineering-Plastics Corporation, and the melt flow rate under 300℃, 1.2kg is 10g / 10min;

[0074] PC resin 3 is PC FG1760 produced by Taiwan Idemitsu, which is a silicon copolymer PC with a siloxane content of 6wt%, and the melt flow rate under 300℃, 1.2kg is 16g / 10min;

[0075] Cellulose nanocrystals 1-6 are all self-made products, and the specific method is as follows:

[0076] Commercially available defatted cotton (average degree of polymerization = 100) is broken into small pieces of 1x1cm, and then 20g is weighed and placed into 200mL of 60-70wt% dilute sulfuric acid aqueous solution, which is mechanically stirred at 40-50℃ and 600rpm for 90min, and then diluted with 1800mL of deionized water, and left to stand for 12h, and the supernatant is removed, and the remaining milky white suspension is centrifuged at 5000rpm for 5min, and the supernatant is removed, and 200mL of deionized water is added and shaken, and the centrifugation process is repeated until no layering occurs, and the obtained white suspension is purified by dialysis in a dialysis bag with a molecular weight cutoff of 8000-14000, until the pH of the deionized water outside the dialysis bag is 6, and the obtained material is concentrated to a solid content of 4wt% using a rotary evaporator, and then 2.2g of the concentrate is dispersed in a 35mm culture dish, and the water is evaporated at 25℃ and 50%RH for 48h, to obtain cellulose nanocrystals, and the average molecular weight of the cellulose nanocrystals is 16200g / mol.

[0077] The cellulose nanocrystal 1 is immersed in a dilute sulfuric acid aqueous solution with a concentration of 68wt% and a temperature of 50°C. The average length of the obtained product is 136 nm, and the average diameter is 8.8 nm.

[0078] The cellulose nanocrystal 2 is immersed in a dilute sulfuric acid aqueous solution with a concentration of 68wt% and a temperature of 48°C. The average length of the obtained product is 245 nm, and the average diameter is 10.3 nm.

[0079] The cellulose nanocrystal 3 is immersed in a dilute sulfuric acid aqueous solution with a concentration of 67wt% and a temperature of 46°C. The average length of the obtained product is 280 nm, and the average diameter is 11.1 nm.

[0080] The cellulose nanocrystal 4 is immersed in a dilute sulfuric acid aqueous solution with a concentration of 66wt% and a temperature of 45°C. The average length of the obtained product is 316 nm, and the average diameter is 11.5 nm.

[0081] The cellulose nanocrystal 5 is immersed in a dilute sulfuric acid aqueous solution with a concentration of 65wt% and a temperature of 42°C. The average length of the obtained product is 370 nm, and the average diameter is 12.4 nm.

[0082] The cellulose nanocrystal 6 is immersed in a dilute sulfuric acid aqueous solution with a concentration of 64wt% and a temperature of 45°C. The average length of the obtained product is 386 nm, and the average diameter is 12.6 nm.

[0083] The cellulose nanocrystal 7 is R186375 produced by Rhone, and the average length is 210 nm, and the average diameter is 10.7 nm.

[0084] The microcrystalline celluloses 1 and 2 are produced by Mccarey, CAS: 9004-34-6, and the average particle sizes are 25 μm and 65 μm, respectively.

[0085] The silicon dioxide powder is a commercially available product, and the average particle size is 500 nm.

[0086] The sulfone polymer 1 is Solvay 5000 produced by Solvay, PPSU, and the melt flow rate under 365°C and 5 kg is 17 g / 10 min.

[0087] The sulfone polymer 2 is BASF P3010 produced by BASF, PPSU, and the melt flow rate under 365°C and 5 kg is 25 g / 10 min.

[0088] The sulfone polymer 3 is Solvay 5800 produced by Solvay, PPSU, and the melt flow rate under 365°C and 5 kg is 30 g / 10 min.

[0089] Sulfone polymer 4 is BASF P2010, PPSU, melt flow rate at 365℃, 5kg is 45g / 10min, produced by BASF Company;

[0090] Sulfone polymer 5 is Solvay P-1700LCD3, PSU, melt flow rate at 365℃, 5kg is 25g / 10min, produced by Solvay Company;

[0091] Sulfone polymer 6 is BASF E 2010G6, PES, melt flow rate at 365℃, 5kg is 25g / 10min, produced by BASF Company;

[0092] The component raw materials used in each embodiment and comparative example of the present application are commercially available raw materials unless otherwise specified, and the component raw materials used in each parallel experiment are the same.

[0093] Table 1

[0094]

[0095] Table 2

[0096] Parts by weight Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Comparative Example 7 PC Resin 1 65 65 65 65 65 65 90 Cellulose Nanocrystal 1 10 Cellulose Nanocrystal 3 10 Cellulose Nanocrystal 6 10 Microcrystalline Cellulose 1 10 Microcrystalline Cellulose 2 10 Silica Powder 10 Sulfone-based Polymer 2 35 35 35 35 35 35 10 Cellulose Nanocrystal Retained Average Length (nm) / 132.5 386.7 / / / 275.3 Cellulose Nanocrystal Retained Average Diameter (nm) / 8.6 12.2 / / / 10.8 Cellulose Nanocrystal Retained Average Aspect Ratio / 15.4 31.7 / / / 25.5

[0097] Effect Example 1

[0098] In order to verify the performance of the product described in the present application, the products of each embodiment and comparative example are subjected to the following performance tests, and the specific steps are as follows:

[0099] (1) Low-temperature toughness retention rate test: after each product is injection molded into a 3.2mm-thick test impact sample, the notched impact strength test is carried out at 25℃ according to ASTM D256-10, type A notch, impact energy 2.75J, to test the normal temperature notched impact strength A0 of the product, then it is placed in a freezer at-23℃ for 48h, quickly taken out and tested by the same method to test the low-temperature notched impact strength A1 of the product, and the low-temperature toughness retention rate of the product is calculated according to 100% x A1 / A0 (rounded to the nearest whole number);

[0100] (2) Heat distortion temperature test: according to ASTM D648-2018 standard, the product is injection molded into a 127x12.7x6.4mm thick test piece, silicone oil is used as heating oil, the heat deflection temperature is determined as the heat distortion temperature, when measuring, the sample is placed on the support in a side-standing manner, the span of the sample support is adjusted to 100±1mm, the load is applied to the middle of the sample to form a simply supported beam structure. Put down the axe-shaped pressure head and make it in good contact with the upper surface of the sample, adjust the loading equipment to the predetermined load, install the deformation measuring device, insert the thermometer, immerse the sample in the silicone oil bath, and heat uniformly at a speed of 2℃ / min, while continuously monitor the deformation of the sample, when the deformation of the middle point of the sample reaches the specified value of 0.25mm, record the temperature of the heating oil at this time (rounded to the nearest whole number), which is the heat distortion temperature;

[0101] (3) Chemical resistance test: the products obtained in each example and the comparative example are injection molded into ASTM D638 Type I (total length 165mm, narrow section width 13mm, thickness 3.2mm) tensile sample strips, the sample surfaces are respectively smeared with the same amount of commercially available rust-proof oil, hand cream and peanut oil, and clamped in a 1 / 4 oval-shaped solvent-resistant stainless steel clamp (the clamp body is a symmetrical metal clamping structure, containing upper and lower two parallel clamping surfaces, the effective span of the clamped sample is the distance between the two clamping points, which is 50±0.5mm, and the deflection of the sample in the span center after clamping is 2.0±0.2mm), the sample surface is observed every 1h until cracks or corrosion marks appear on the sample surface, and the chemical solvent immersion retention time of the sample is recorded. The shortest immersion retention time of the three is recorded (in hours, for example, the sample surface is normal at 140h observation, and cracks or corrosion marks appear at 141h observation, the retention time of the sample is recorded as 140h).

[0102] The test results are shown in Tables 3 and 4.

[0103] Table 3

[0104]

[0105] Table 4

[0106] Test Performance Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Comparative Example 7 Low Temperature Notched Impact Strength Retention (%) 30 80 82 55 54 32 70 Heat Distortion Temperature (°C) 119 125 126 123 121 125 128 Retention Time (h) 6 20 22 15 16 12 19

[0107] As can be seen from Tables 3 and 4, the PC composition described in the application constructs an organic resin system by compounding a sulfone polymer and a PC resin, and introduces cellulose nanocrystals as a skeleton material while limiting the aspect ratio thereof. The PC composition can effectively improve the chemical solvent resistance of the product, and can be applied to various products that are in long-term contact with chemical solvents, regardless of whether the chemical solvent is a chemical rust-proof oil, a cosmetic hand cream, or a food peanut oil. The shortest stable time of the product during aging immersion can reach 22 hours or more, and the chemical inertness is high. On the other hand, the notched impact strength retention rate of the product at -23°C is 90% or more than that at room temperature, indicating that the product has good low-temperature resistance and does not fail in low-temperature toughness. The pressure heat distortion temperature of the product is 130°C or more, and the product has good high-temperature resistance and excellent comprehensive performance.

[0108] In contrast, the product of Comparative Example 1 does not introduce cellulose nanocrystals, and the chemical solvent resistance and high and low temperature resistance of the product containing a sulfone polymer are not good. The products of Comparative Examples 4 to 6 introduce common microcrystalline cellulose and silica powder as skeleton ingredients on the basis of the product of Comparative Example 1, but they do not have the same reinforcing performance effect as cellulose nanocrystals, and the performance of the products does not reach the expected level.

[0109] As can be seen from the performance comparison of the products of Example 1, Examples 4 to 6, and Comparative Examples 2 to 3, the aspect ratio of cellulose nanocrystals in the product directly affects the performance of the product. If the aspect ratio is too large or too small, as shown in Comparative Examples 2 to 3, the product cannot achieve the performance of the product of the examples and cannot have good chemical resistance and high and low temperature resistance. When the aspect ratio of cellulose nanocrystals is controlled within the limited range of 20 to 30, and is further preferably 24 to 28, the reinforcing effect of the cellulose nanocrystals is better, the uniformity and regularity of the creep of the organic molecules in the product when the temperature changes are better, and the high and low temperature resistance is better.

[0110] As can be seen from Comparative Example 7, the introduction of a sulfone polymer is also crucial in addition to cellulose nanocrystals. If the amount of the sulfone polymer introduced is too small, the chemical resistance and high and low temperature resistance of the product are not ideal. When the amount of the sulfone polymer introduced is controlled within the limited range of the application, as can be seen from Example 1 and Examples 7 to 11, the performance of the product prepared from different types of sulfone polymers is different. The performance effect of PPSU is better, and the organic phase structure of the product after being compatible with the PC resin is different when the melt index of the sulfone polymer changes. When the melt index of the sulfone polymer is preferably within the range of 20 to 30 g / 10 min, the performance of the product can be further improved.

[0111] Finally, it should be noted that the above examples are merely intended to illustrate the technical solutions of the present application and not to limit the protection scope of the present application. Although the present application has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present application can be modified or equivalently replaced without departing from the essence and scope of the technical solutions of the present application.

Claims

1. A PC composition, characterized in that, The components include the following parts by weight: 60-70 parts PC resin, 1-20 parts cellulose nanocrystals, and 30-50 parts sulfone polymers; The aspect ratio of the cellulose nanocrystals is 20–30.

2. The PC composition according to claim 1, characterized in that, The melt flow rate of the PC resin at 300℃ and 1.2kg load is 6-18g / 10min.

3. The PC composition according to claim 1, characterized in that, The PC resin includes at least one of silicone copolymer PC resin and bisphenol A type copolymer PC resin.

4. The PC composition according to claim 1, characterized in that, The aspect ratio of the cellulose nanocrystals is 24–28.

5. The PC composition according to claim 4, characterized in that, In the PC composition, the average length of the retained cellulose nanocrystals is 200–400 nm, and the average diameter is 10–15 nm.

6. The PC composition according to claim 1, characterized in that, The sulfone polymers include at least one of polysulfone, polyphenylene sulfone, and polyether sulfone.

7. The PC composition according to claim 1, characterized in that, The sulfone polymer has a melt index of 15-50 g / 10 min at 365°C and 5 kg load.

8. The method for preparing the PC composition according to any one of claims 1 to 7, characterized in that, Includes the following steps: After the components are mixed evenly, they are melt-extruded and granulated in a screw extruder to obtain the PC composition.

9. The application of the PC composition according to any one of claims 1 to 7 in the preparation of outer packaging materials; preferably, the outer packaging material includes any one of automotive outer shell parts, electronic and electrical outer shell parts, food packaging shells, and daily chemical product packaging shells.

10. A type of outer packaging material, characterized in that, Includes the PC composition according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Biodegradable fiber reinforced PC / ABS composite material

    CN111087787A

  • PC / PET alloy material, preparation method and application thereof

    CN118772614A

  • Polycarbonate composite material, display screen mask and outdoor LED display screen

    CN119081379A

  • Polycarbonate composition as well as preparation method and application thereof

    CN119931301A

  • Flame-retardant resin composition and molding

    JP2020070332A